Javanese Script Writing Training as a Form of Local Cultural Conservation for Tanjung Community, Special Region of Yogyakarta - Harto Wicaksono; Ninuk Solikhah Akhiroh; Fadly Husain; Didi Pramono; Siti Khuzaimah; Nekha Dewi Anggraeni; Zidane Atala Naufal; Ghisya Sauqina Rosyada (Universitas Negeri Semarang, 2024)
Javanese script is a cultural heritage from our ancestors that needs to be preserved. Javanese script is often introduced to the education system in the form of local educational content such as in Javanese language subjects. Even so, there are still many people who are not interested in learning it, because writing Javanese script has a fairly high level of complexity. The rules in writing starting from the shape of the letters, giving pairs, and sandhangan are factors that make people less interested in learning Javanese script. This certainly affects the existence of Javanese script today. Therefore, such a situation should not be allowed to continue because it can eliminate the identity and locality of the community which has an impact on the fading of cultural entities. In response to this situation, reinforcement is needed in the form of Javanese script writing training. This activity is an important part of efforts to conserve local culture. Like this service which was carried out in Padukuhan Wukirsari, Cangkringan, Sleman, Yogyakarta. The implementation methods used in this community service program are socialization, Focus Group Discussion (FGD), and training/simulation. With this program, the community can be fostered, empowered, and begin to be independent in learning to use Javanese script as their cultural identity.